Integrative Review of Qualitative Research on the Emotional Experience of Bullying Victimization in Youth - Hutson, Elizabeth (J Sch Nurs, 2017)
The emotional experience of bullying victimization in youths has been documented primarily using quantitative methods; however, qualitative methods may be better suited to examine the experience. An integrative review of the qualitative method studies addressing the emotional experience of bullying victimization was conducted. From MEDLINE, Cumulative Index of Nursing and Allied Health Literature, PubMed, Education Information Resource Center, and PsycINFO, 14 English-language, peer-reviewed, qualitative studies were reviewed. Applying the Critical Appraisal Skills Programme, the quality of the studies was deemed sufficient. The range of emotional experiences reported included sadness, decreased self-esteem, embarrassment, fear, suicidal thinking, anger, feeling hurt, loneliness, powerlessness, helplessness, and confusion. Overall, these results were similar to those obtained from quantitative method studies, apart from the feeling of embarrassment. This integrative review confirmed and expanded the knowledge of emotional experiences of bullying victimization.